RESPONSE OF WHEAT (Triticum aestivum L.) TO DIFFERENT MICRONUTRIENTS AND THEIR APPLICATION METHODS - M. A. Nadim; I. U. Awan; M. S. Baloch; E. A. Khan; K. Naveed; M. A. Khan (Journal of Animal and Plant Sciences, 2012)
Growth and yield response of wheat variety Gomal-8 was evaluated using micronutrients and their application methods. The trial was laid out in a randomized complete block design with split-plot arrangements. Five different micronutrients were placed in main plot while their three application methods were assigned to sub-plots. Results revealed that application of boron @ 2 kg ha-1 produced higher crop growth rate (23.58 g m-2 day-1), net assimilation rate (2.82 mg m-2 day-1), number of tillers (234.5 m-2), number of grains (52.92 spike-1) and grain yield (3.14 t ha-1). The use of iron @ 12 kg ha-1 also showed encouraging results similar to boron. Among various application methods, side dressing at 4 weeks after sowing (WAS) showed the best results as compared to soil application and foliar spray. Higher leaf area index and crop growth rate was obtained with the application of zinc @ 10 kg ha-1. Also, different micronutrients had significant interaction with application methods for physiological and agronomic traits including number of tillers, leaf area index (LAI), crop growth rate (CGR), net assimilation rate (NAR) and grain yield. Side dressing best interacted with boron for producing higher number of tillers, grains per spike, net assimilation rate and grain yield. This method showed better combination with iron for higher number of tillers, LAI and grain yield.
Keywords: Wheat; micronutrients; application methods; growth; LAI.